Preparation of C60 Nanowhiskers/NiS2 Nanocomposites and Photocatalytic Degradation of Organic Dyes - Hyung Kim, Keun; Bae Ko, Weon (Asian Journal of Chemistry, 2015)
[C60]Fullerene nanowhiskers/NiS2 nanocomposites were prepared by a reaction of NiS2 nanoparticles and C60 nanowhiskers. The C60 nanowhiskers (FNWs) were synthesized by a liquid-liquid interfacial precipitation method using solvent solutions, such as benzene and toluene saturated with C60 powder and isopropyl alcohol. The NiS2 nanoparticles were synthesized by a reaction of NiCl2·H2O and Na2S2O3·5H2O in deionized water under microwave irradiation. The C60 anowhiskers/NiS2 nanocomposites were calcined in an electric furnace at 700 °C for 2 h. The C60 nanowhiskers/NiS2 nanocomposites were characterized by X-ray diffraction and UV-visible spectrophotometry. The C60 nanowhiskers/NiS2 nanocomposites were evaluated as a photocatalyst by UV-visible specrophotometry in the degradation of organic dyes, such as methylene blue and brilliant green, under ultraviolet light at 365 nm.